Sequence analysis of amphotropic and 10A1 murine leukemia viruses: close relationship to mink cell focus-inducing viruses. - Ott, D (1990)
Viral interference studies have demonstrated the existence of four distinct murine leukemia virus (MuLV) receptors on NIH 3T3 mouse cells. The four viral interference groups are ecotropic MuLV; mink cell focus inducing virus (MCF); amphotropic MuLV; and 10A1, a recombinant derivative of amphotropic MuLV that uses a unique receptor but also retains affinity for the amphotropic MuLV receptor. We report here that 10A1 infects rat and hamster cells, unlike its amphotropic parent. We isolated an infectious molecular clone of 10A1 and present here the sequences of the env genes and enhancer regions of amphotropic MuLV and 10A1. The deduced amino acid sequences of amphotropic MuLV and 10A1 gp70su are remarkably similar to those of MCF and xenotropic MuLV (for which mouse cells lack receptors), with 64% amino acids identical in the four groups. We generated a consensus from these comparisons. Further, the differences are largely localized to a few discrete regions: (i) amphotropic MuLV has two short insertions relative to MCF, at residues 87 to 92 and 163 to 169, and (ii) amphotropic MuLV and MCF are totally different in a hypervariable region, which is greater than 30% proline, at residues approximately 253 to 304. 10A1 closely resembles amphotropic MuLV in its N terminus but contains an MCF-type hypervariable region. These results suggest the possibility that receptor specificity is localized in these short variable regions and further that the unique receptor specificity of 10A1 is due to the novel combination of amphotropic MuLV and MCF sequences rather than to the presence of any novel sequences. The Env proteins of ecotropic MuLV are far more distantly related to those of the other four groups than the latter are to each other. We also found that the enhancer regions of amphotropic MuLV and 10A1 are nearly identical, although 10A1 is far more leukemogenic than amphotropic MuLV.